ANALISIS FRONTIER EFFICIENCY INDUSTRI PERBANKAN INDONESIA DENGAN MENGGUNAKAN METODE DISTRIBUTION FREE APPROACH - Agus Herta Sumarto; Iman Sugema (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2013)
As an intermediary institution, bank has a very vital role in the economic development of a country so bank has to operate efficiently. The efficiency analysis can be conducted with the three approaches, namely cost efficiency, profit efficiency, and alternative profit efficiency. The three approaches can measured with two methode, parametric and non parametric. By using parametric methode (Distribution Free Approach), cost efficiency of 107 commercial banks operating for 10 years (2002- 2011), the average cost efficiency of banks in Indonesia is 0.6729. While the average value of the profit efficiency in Indonesian banks is 0.96363 or more efficient than cost efficiency. The score of alternative profit efficiency Indonesian banks is 0.965957. The cost efficiency of commercial banks on average have no strong correlation with all financial ratios of banks. The profit efficiency have a strong relationship with financial ratios ROA and BOPO. Financial performance of the bank's ROE ratio has a moderate correlation with the level of profit efficiency. While the level of alternative profit efficiency have a strong relationship with financial performance ratios ROE, ROA, and ROA. NIM ratio has a low relationship with alternative profit efficiency. Keyword: Distributin Free Approach, Cost Efficiency, Profit Efficiency, and Alternative Profit Efficiency.